Potential wound healing activity of Quercus infectoria formulation in diabetic rats - Chokpaisarn,Julalak; Chusri,Sasitorn; Amnuaikit,Thanaporn; Udomuksorn,Wandee; Voravuthikunchai,Supayang Piyawan (PeerJ, 2017)
Background Quercus infectoria G. Olivier (Fagaceae) nutgalls have been widely employed in traditional Asian medicine for several treatments, especially wounds and skin disorders. However, the effects of this plant on wound healing have not yet been clearly elucidated. This present work was focused on utilization of Quercus infectoria (Qi) as a topical agent for chronic wound treatment. Methods Twenty Qi formulations (QiFs) were pharmaceutically formulated and antibacterial activity of all formulations was performed. The best formulation based on an antibacterial activity was selected for evaluation of wound healing property. Total phenolics, total flavonoids, and an anti-oxidant activity of the selected formulation were also investigated. Wound healing activity was assessed in streptozotocin-induced diabetic rats and control rats. Streptozotocin injection (50 mg/kg) was found to induce marked hyperglycaemia, compared with citrate-injected controls. Two wounds were created on the upper back of each animal. QiF was topically applied three days after wounding to one of the duplicate wounds on each animal and physiological saline (control) was applied to the other. All wounds were cleaned once a day until wound closure. Results QiF10, which exhibited antibacterial and anti-oxidant activities, had the ability to enhance the wound healing process in diabetic rats with abundant cellular infiltration, collagen deposition, and re-epithelialization when compared with the control. Discussion This study suggested that QiF10 could be a novel alternative treatment for diabetic wounds.
Keywords: Diabetic wounds; Quercus infectoria; Wound healing process; Wound treatment